The Development of Thermoresponsive Multifunctional Chitosan Films Suitable for Food Packaging - Nihal Sarier; Anıl Eloglu; Emel Onder (Polysaccharides)
We developed bio-based chitosan–gelatin films, CHG-LO films, incorporating lavender essential oil (15–26 wt% LO) and oleic acid (33–47 wt% OA) with smooth surfaces and thicknesses of 0.42–0.99 mm. For their manufacture, the nanoemulsions were prepared to possess uniform dispersion and colloidal stability with average droplet sizes of 475–854 nm, polydispersity indices (PDI) of 0.095–0.235, and zeta potentials of 23.7–56.9 mV at 40 °C, where OA served as surfactant and phase change material. The opacities of the CHG-LO films increased by 1.8 to 5.5 times compared to the control group, and their UV-visible light-blocking properties improved. These films demonstrated cyclic thermal buffering character, with heat storage capacities ranging from 14.0 to 36.0 J·g−1 between −26 °C and 20 °C compatible with that of OA. Additionally, they showed reduced water vapor transmission rates and swelling degrees in acidic and neutral environments. The total phenolic contents of the CHG-LO films increased 1.5–4.2 times compared to the control associated with the presence of LO phenolic groups in the structure. DPPH (2,2-diphenyl-1 picrylhydrazyl) and ABTS (2,2′–azino–bis(3–ethylbenzothiazoline–6–sulphonic acid)) scavenging activity test results show that the antioxidant properties of these films improved with increasing LO-OA content up to 2.2 and 1.3 times the control, respectively, and also showed antimicrobial properties. The multifunctional CHG-LO films of this study are promising candidates for temperature-sensitive active packaging in food as well as in pharmaceutical and cosmetic industries.